2017
DOI: 10.1007/s00421-017-3679-9
|View full text |Cite
|
Sign up to set email alerts
|

Beta2-adrenergic stimulation increases energy expenditure at rest, but not during submaximal exercise in active overweight men

Abstract: Selective β-adrenoceptor agonism effectively increases metabolic rate and fat oxidation in overweight individuals. The potential for weight loss induced by β-agonists may be greater for R-enantiopure formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
43
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 44 publications
3
43
0
Order By: Relevance
“…This observation underpins the efficacy of formoterol in activating beta 2 ‐adrenergic signaling pathways in skeletal muscle, even after inhalation in therapeutic doses. The formoterol‐induced PKA signaling in skeletal muscle likely explains the apparent effects of formoterol on protein turnover and substrate utilization observed in previous studies …”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…This observation underpins the efficacy of formoterol in activating beta 2 ‐adrenergic signaling pathways in skeletal muscle, even after inhalation in therapeutic doses. The formoterol‐induced PKA signaling in skeletal muscle likely explains the apparent effects of formoterol on protein turnover and substrate utilization observed in previous studies …”
Section: Discussionmentioning
confidence: 71%
“…It should also be noted that compared to rac‐ salbutamol, the muscle:plasma partition coefficient ( K m ) for rac‐ formoterol in the present study was greater than that previously reported in a rodent model for oral dosing of salbutamol (14.3 versus 3.8), acknowledging that the route of administration (oral) and sampling (4 hours) were also different. This greater partitioning could be a pharmacokinetic factor for consideration of formoterol as a preferential therapeutic for muscle wasting and obesity or doping misuse compared to the short acting salbutamol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is highly relevant for doping control as formoterol is delivered by inhalation for therapeutic use and a threshold for total formoterol (free and glucuronide conjugate) is used . Supratherapeutic dosing of beta2‐agonists via the inhaled route has been shown to elicit performance‐enhancing effects as well as increase fat oxidation …”
Section: Introductionmentioning
confidence: 99%